Conservação, biodiversidade e bioeconomia: discursos neoliberais e a “Ecologia da Plantation” da soja na Amazônia - NUNES, Adriana (Universidade Federal do Pará, 2024)
This doctoral thesis studies and analyzes the power-knowledge relations and devices that have created in the Amazon an idea of dominant conservation, with a state character, based on the decarbonization of production processes, changes in land use, and the commoditization of the forest and its biodiversity and ecosystem services. In times of facing the bioclimatic crisis, and the Amazon itself is threatened with collapse, the most recent global political-scientific discourse advocates transformative changes in the relationship between society and nature, notably in the global economic model, capable of resolving the climate crisis, paralyzing the loss of planetary biodiversity and provide sustainable development, a Great Reset. The research object is, in turn, centered on public policies seen as transformative and, at the same time, conciliatory of development and forest conservation in a soybean frontier in the Amazon and at the same time considered a laboratory of public conservation policies, from which new notions and appropriations of global discourse emerge, such as “skills ecology”, “ecoefficiency”, “efficient landscape”, and more broadly, “forest restoration”, “carbon neutral”, “low-energy economy”. carbon”, “sustainable transition” and “Bioeconomy”. The main empiric of the research is the “Municipal Model of Development and Territorial Intelligence of Paragominas”, in the state of Pará, more specifically the conservation of Legal Reserve (RL) areas of private rural properties. The theoretical instrument of the thesis is interdisciplinary, combining knowledge from biological sciences and analytical studies of power and discourse in the human sciences. The methodological options bring together the overlapping of spatial scales, bibliographic and documentary analysis, semi-structured interviews, and mapping of power-knowledge relationships and devices put in place in the name of conservation, dynamic between the State, companies, institutions, NGOs, and other actors. It is argued in this thesis that a new global social order, which not only includes conservation, but holds within it the condition of possibility for maintaining neoliberal practices of domination of space and its resources, is underway. This new sense of conservation, socially produced, offers technical solutions to crises that arise from serious political problems such as inequality of access and use of natural resources, imposing knowledge that promotes market environmentalism, and does not act on real drivers. At the same time, they make invisible the practices of social agents, who through their ways of life ensure biological, social, cultural and economic diversity, becoming dominant over practices based on the common principle. We conclude that the Amazon has been the scene of an impostor conservation, based on “technosciences”, which uses the practice of abandoning other areas to regeneration to destroy the LR, converting the forest and its biodiversity into soybeans and other agricultural commodities; it expropriates and pulverizes local family farming communities and prioritizes actors and sectors associated with export commodities, in public development policies and confronting the bioclimatic crisis. The “ecology” present in the “aptitude maps”, “eco-efficient conservation” and transition/transformation of sustainable agriculture constitutes a “Plantation Ecology” of soy, which goes beyond the region, as it is organized and benefits power groups of instances, organizations and institutions in addition to the certified and traceable landscapes of Paragominas. The results of the five (5) chapters produced constitute an effort to show through which processes the practices that transmute deforestation, destruction of socio-biodiversity and concentration of monetary and non-monetary benefits, in power groups, into conservation discourses are organized.